Quantification of mechanical vibration during diffusion tensor imaging at 3 T - Hiltunen, Jaana; Hari, Riitta; Jousmäki, Veikko; Müller, Kiti; Sepponen, Raimo; Joensuu, Raimo (NeuroImage (Orlando, Fla.), 2006)
Subjects sense clear mechanical vibrations during diffusion tensor imaging (DTI). These vibrations, likely resulting from diffusion-sensitizing gradients, have been assumed to be of the same strength and phase in all parts of the magnetic resonance imaging (MRI) scanner so that they could be ignored. However, our measurements, carried out from several parts of the MRI scanner and its surroundings using an optical laser-based interferometer, demonstrate an uneven distribution of mechanical vibrations within the scanner. The measurements were performed during DT scanning at 3 T, with various diffusion-weighting parameters, by positioning a phantom in the head coil and/or a human subject on the patient bed. The vibration-related movement was caused by the diffusion-sensitizing gradients and was maximally 0.5 mm with typical settings used in brain imaging. The compensation for eddy currents, done with gradients in our DTI sequence, increased the vibration level by a factor of 1.5 or more with diffusion-weighting parameter b = 1000 s/mm 2 and by a factor of 3 or more with b = 3000 s/mm 2. Mechanical vibrations stayed at an acceptable level with b ≤ 1000 s/mm 2, resulting in additional signal losses of 5–17%. Vibration levels might be reduced by adjusting imaging parameters, by modifying the gradient waveforms in the DTI sequence, and by redesigning the mechanics of patient bed to effectively dampen the movements.